Improving Political Behavior Through Group Counseling Services with Sociodrama Techniques in Schools - Muhammad Farid Ilhamuddin; Issac Briyan Alisyahbana (Indonesia Approach Education, 2020)
Sociodrama technique is a method of role-playing learning to solve problems related to social phenomena. The use of sociodrama techniques in this study is to improve the polite behavior of students through group guidance services. This study uses action research, with two cycles, namely cycle 1 and 2, each of which has two meetings and at each meeting allocates 40 minutes. Data collection methods used are observation, interviews, and documentation to determine the level of politeness of students in the implementation of group guidance services in school. The subjects of the study were ten students from grade 8th, Unesa Middle School who had problems in their polite behavior. Based on the observations of students in both cycles, there is an increase in the politeness of students, including good criteria in the implementation of group guidance services using Sociodrama techniques. After the implementation of the first cycle, it can be seen that there is a 63% change in students' behavior which means it shows the politeness behavior of students in the Good Criteria. At the meeting, after the second cycle, there is an increase to 76% in the Good criteria. Thus, from the results of the analysis, it can be concluded that the action research hypothesis that reads